Prognostic value of molecular markers of oral pre-malignant and malignant lesions - Peter Agus (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: The representation of oral cancer and precancerous lesions is often undetected until at later stage and the survival rate of oral cancer has remained essentially unchanged over the past three decades. Over 90% of these tumors are squamous cell carcinoma. The American Cancer Society estimates that among 28,900 new cases of oral diagnosis in 2002, nearly 7,400 people will die from this disease. Oral pre-malignant and malignant lesions have multi-step process both at phenotype and genetic levels that influence tumor behavior and genetic mutations. Purpose: The aim of this presentation was to review the current knowledge of prognostic value of tumor marker in order to achieve early detection, prognostic value, proper and accurate treatment of oral cancer. Reviews: Technological advances in molecular biology have greatly increased the number of new molecular markers that can be detected by molecular analysis such as immunohistochemistry (IHC), polymerase chain reaction (PCR) and surgical margin analysis that may increase prognosis and treatment of oral cancer. The result of most valuable tumor markers is twenty nine divided into four groups according to their function such as enhancement of tumor growth, tumor suppression and anti tumor defense, including immune response and apoptosis, angiogenesis, tumor invasion and metastatic potential, including adhesion molecules and matrix degradation. Conclusion: In general the conclusion is that the location of markers within the tumor and not the quantitative assessment is as same as emphasized. Especially, the analysis of new molecular markers have been used to be of great importance for early detection, surgical margin analysis, prognostication and treatment of oral pre-malignant and cancerous lesion.